2018
DOI: 10.1016/j.jhydrol.2018.08.063
|View full text |Cite
|
Sign up to set email alerts
|

Climate-driven trends in the streamflow records of a reference hydrologic network in Southern Spain

Abstract: Monthly streamflow records from a set of gauging stations, selected to form a reference hydrologic network, are analyzed together with precipitation and temperature data to establish whether the streamflows in the Guadalquivir River Basin have experienced changes during the last half of the XXth century that can be attributed to hydrological forcing. The observed streamflows in the reference network have undergone generalized and significant decreases both at seasonal and annual scales during the study period.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
1
17
0
3
Order By: Relevance
“…As a region characterized by semiarid conditions, the interest of ET o in Spain is apparent, and many studies addressed different topics related with this variable. Until now, ET o studies in Spain focused on a limited number of locations (Vicente‐Serrano et al ., 2014b; Azorin‐Molina et al ., 2015; Tomas‐Burguera et al ., 2017), or used only temperature to estimate ET o following the Hargreaves and Samani (Hargreaves and Samani, 1985) approach (Berengena and Gavilan, 2005; Vanderlinden et al ., 2008; Aguilar and Polo, 2011; Giménez and García‐Galiano, 2018; Yeste et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As a region characterized by semiarid conditions, the interest of ET o in Spain is apparent, and many studies addressed different topics related with this variable. Until now, ET o studies in Spain focused on a limited number of locations (Vicente‐Serrano et al ., 2014b; Azorin‐Molina et al ., 2015; Tomas‐Burguera et al ., 2017), or used only temperature to estimate ET o following the Hargreaves and Samani (Hargreaves and Samani, 1985) approach (Berengena and Gavilan, 2005; Vanderlinden et al ., 2008; Aguilar and Polo, 2011; Giménez and García‐Galiano, 2018; Yeste et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Countries bordering the northeast Atlantic Ocean (Spain, Portugal, France, the United Kingdom, and Ireland) are highly sensitive to changes in climate (natural and human forced) and hydrology, with the region having a high population density and intense water use (Thober et al, ). In southwestern Europe, water scarcity is frequent as a consequence of climatic drought events (González‐Hidalgo et al, ), with consequences aggravated by the general reduction in streamflow recorded over recent decades (Coch & Mediero, ; García‐Ruiz et al, ; Lorenzo‐Lacruz et al, ; Yeste et al, ). These decreasing trends are likely to have caused more severe hydrological droughts (Vicente‐Serrano, Lopez‐Moreno, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent pan-European studies Masseroni et al (2020) and Stahl et al (2010) both found downward river flow trends in the southern and eastern parts of Europe, whereas positive trends were determined in northern areas of the continent. Such patterns of river discharge changes have also been confirmed by studies on a lower scale -in Spain (Yeste et al, 2018), Italy (Billi and Fazzini, 2017), the United Kingdom (Hannaford and Buys, 2012), the Nordic Region (Wilson, et al, 2010), etc. Streamflow trends research over southeastern part of Europe, conducted at different spatial scales, also suggest downward tendencies of streamflow in this region.…”
Section: Introductionmentioning
confidence: 63%